MUHAMMAD YUSUF WAS A SIMPLE AND SIMPLE UZBEK POET - Nargiz Jurayeva Tilovmurodovna (American Journals, 2023)
This article is about the sincerity and simplicity of the poet Muhammad Yusuf, his beautiful and elegant, unique and incomparable poetry collections and life path that appeal to every language and language, old and young alike. the word goes
Keywords: silence, emotional painterly simplicity, echo